Laquinimod Safety Profile: Pooled Analyses from the ALLEGRO and BRAVO Trials - Sørensen, Per Soelberg (Int J MS Care, 2017)
BACKGROUND: Laquinimod 0.6 mg is a once-daily, oral, disease-modifying therapy in development for the treatment of multiple sclerosis (MS) that was investigated in two double-blind, placebo-controlled, phase 3 trials: ALLEGRO and BRAVO. METHODS: Data from these studies were pooled to assess the safety profile of laquinimod versus placebo. Adverse events (AEs), laboratory value changes, and potential risks identified in preclinical studies were evaluated in participants in ALLEGRO and BRAVO treated with at least one dose of laquinimod or matching placebo (1:1 random assignment). RESULTS: In total, 1988 patients received at least one dose of study drug (laquinimod: n = 983 [mean ± SD duration, 639 ± 190 days]; placebo: n = 1005 [mean ± SD duration, 627 ± 198 days]). Early terminations due to AEs were infrequent (laquinimod: 6.4%; placebo: 4.7%). Death was reported in four patients (laquinimod: n = 1; placebo: n = 3). Rates of serious AEs (including malignancies, infections, and cardiovascular AEs) were similar between groups. The most common AEs identified with laquinimod use were back and neck pain and appendicitis. Laquinimod was also associated with asymptomatic changes in liver enzyme levels, fibrinogen levels, and hematologic parameters that followed a consistent temporal pattern: mild, nonprogressive, and occurring within 90 days of treatment initiation, then stabilizing or reverting to baseline levels during continued treatment. CONCLUSIONS: Data from these pivotal laquinimod studies demonstrate a safety profile comprising benign or manageable AEs and asymptomatic laboratory findings with a clear temporal pattern. Potential risks noted in preclinical studies were not observed.